2019
DOI: 10.2298/vsp170422156s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nursing care-associated predictors of in-hospital mortality in the patients with acute ischemic stroke

Abstract: Background/Aim. Stroke remains one of the leading causes of death and disability worldwide. The aim of the study was to determine the nursing care-associated predictors of in-hospital mortality in the patients with acute ischemic stroke (AIS) who were hospitalized at the Department of Emergency Neurology. Methods. Prospective cohort study included 59 consecutive patients with AIS admitted to the Department of Emergency Neurology, Neurology Clinic, Clinical Center of Serbia, Belgrade. The patients were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
2
0
3
Order By: Relevance
“…Además, se han investigado las experiencias y percepciones de las enfermeras en el cuidado de pacientes con ICTUS. Se ha observado que las enfermeras identifican una brecha entre su papel ideal en el cuidado y su práctica real, experimentando sentimientos encontrados que pueden afectar tanto psicológicamente como básicamente a las enfermeras [41,42,44] .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Además, se han investigado las experiencias y percepciones de las enfermeras en el cuidado de pacientes con ICTUS. Se ha observado que las enfermeras identifican una brecha entre su papel ideal en el cuidado y su práctica real, experimentando sentimientos encontrados que pueden afectar tanto psicológicamente como básicamente a las enfermeras [41,42,44] .…”
Section: Discussionunclassified
“…El principio enfatiza la urgente necesidad de detección y tratamiento tempranos en pacientes con sospecha de accidente cerebrovascular [10] . Es importante que las enfermeras puedan reconocer tempranamente las manifestaciones del ictus y determinar la aparición de los signos y síntomas para garantizar que los pacientes puedan recibir el tratamiento adecuado en un plazo determinado [11] . Según la Asociación Estadounidense del Corazón (AHA) y el Grupo de Consenso Europeo, los pacientes con ICTUS necesitan atención médica inmediata.…”
Section: Pág 694unclassified
See 1 more Smart Citation
“…Furthermore, the use of several stroke scales can also be beneficial to detect stroke manifestations and assess the severity of a stroke [ 8 ]. Several studies have suggested that the National Institutes of Health Stroke Scale (NIHSS) is effective, and it is widely used, easy to learn, and rapidly completed on admission.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies on the early management of patients with stroke, one of the important members of the stroke-management team is the nursing staff [ 8 ]. Stroke nurses are well prepared to provide urgent care for stroke patients.…”
Section: Introductionmentioning
confidence: 99%